Age-Related Reduced Somatosensory Gating Is Associated with Altered Alpha Frequency Desynchronization. (31st August 2015) - Cheng, Chia-Hsiung; Chan, Pei-Ying S.; Baillet, Sylvain; Lin, Yung-Yang
Abstract : Sensory gating (SG), referring to an attenuated neural response to the second identical stimulus, is considered as preattentive processing in the central nervous system to filter redundant sensory inputs. Insufficient somatosensory SG has been found in the aged adults, particularly in the secondary somatosensory cortex (SII). However, it remains unclear which variables leading to the age-related somatosensory SG decline. There has been evidence showing a relationship between brain oscillations and cortical evoked excitability. Thus, this study used whole-head magnetoencephalography to record responses to paired-pulse electrical stimulation to the left median nerve in healthy young and elderly participants to test whether insufficient stimulus 1- (S1-) induced event-related desynchronization (ERD) contributes to a less-suppressed stimulus 2- (S2-) evoked response. Our analysis revealed that the minimum norm estimates showed age-related reduction of SG in the bilateral SII regions. Spectral power analysis showed that the elderly demonstrated significantly reduced alpha ERD in the contralateral SII (SIIc). Moreover, it was striking to note that lower S1-induced alpha ERD was associated with higher S2-evoked amplitudes in the SIIc among the aged adults. Conclusively, our findings suggest that age-related decline of somatosensory SG is partially attributed to the altered S1-induced oscillatory activity.